2023
DOI: 10.1097/yco.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

Social contagion, violence, and suicide among adolescents

Abstract: Purpose of reviewSocial Contagion is defined as the spread of behaviors, attitudes, and affect through crowds and other types of social aggregates from one member to another. Adolescents are prone to social contagion because they may be especially susceptible to peer influence and social media.In this article, we provide a brief review of the most recent findings on social contagion, violence, and suicide among adolescents.Recent findingsRecent evidence support social contagion in gun violence, bullying, cyber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Social contagion is a phenomenon defined as "the spread of behaviors, attitudes, and affect through crowds and other types of social aggregates from one member to another" (Martínez, Jiménez-Molina, and Gerber 2023). Some have attributed the spread of various harmful behaviors and attitudes to social contagion, such as violent tendencies, risk-taking behaviors, suicidality, and eating disorders (Martínez, Jiménez-Molina, and Gerber 2023;Abraham et al 2022;Hilton 2018). Research surrounding the phenomena of social and behavioral contagion has been well established, rooted specifically in observed clusters of suicidality (Guidry et al 2021).…”
Section: Social Contagion and Suicidementioning
confidence: 99%
“…Social contagion is a phenomenon defined as "the spread of behaviors, attitudes, and affect through crowds and other types of social aggregates from one member to another" (Martínez, Jiménez-Molina, and Gerber 2023). Some have attributed the spread of various harmful behaviors and attitudes to social contagion, such as violent tendencies, risk-taking behaviors, suicidality, and eating disorders (Martínez, Jiménez-Molina, and Gerber 2023;Abraham et al 2022;Hilton 2018). Research surrounding the phenomena of social and behavioral contagion has been well established, rooted specifically in observed clusters of suicidality (Guidry et al 2021).…”
Section: Social Contagion and Suicidementioning
confidence: 99%
“…Adolescents find themselves increasingly drawn to their devices, seeking validation and affirmation through the digital realm. A study by Kuss and Griffiths [7] suggests that addictive social media use is linked to higher levels of anxiety, depression, and feelings of loneliness among adolescents [7] meanwhile [8] carried a study on this similar topic and found out that evidence supports social contagion in gun violence, bullying, cyberbullying, violent offending, and suicide. They therefore argued that social learning, identification with significant others, and the normalization of specific norms play a role.…”
Section: Addiction and Mental Healthmentioning
confidence: 99%
“…Another prominent example of network analysis in suicide research is the detection of suicide clusters from temporal social networks. As emphasized by recent research, "mechanisms underlying the contagion effect of suicidal thoughts and behavior are currently unclear" [72]. In contrast, network simulations create computer-generated data based on explicit mechanisms.…”
Section: Microsimulation Network Simulation and Discrete Event Simula...mentioning
confidence: 99%